Development of Non-Destructive Testing for Hydraulic Metal Structures and the Application of Phased Array Ultrasonic Technology - Ji, Bolin (Exploring Science Academic Conference Series, 2026)
Against the background of increasingly complex operating conditions and the aging of early equipment in hydraulic metal structures, conducting preventive non-destructive testing is of great significance for ensuring the safe operation of water conser vancy and hydropower projects. Compared with traditional inspection methods, phased array ultrasonic technology effectively overcomes the limitations of conventional techniques, such as large inspection blind zones and radiation hazards. This technology has demonstrated high reliability and significant practical value in addressing engineering challenges including full -coverage scanning of complex welds, inspection of special materials in turbine runners, and detection of high -strength bolts. The widespread application of phased array ultrasonic technology not only effectively identifies defects in deep structural regions but also provides a more scientific and modern inspection approach for ensuring the safety of hydraulic metal structures.